2000
DOI: 10.1080/08958378.2000.11463204
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Analysis of the Relationship Between Mortality and the Chemical Composition of Airborne Particulate Matter

Abstract: We explored relationships between daily mortality and the major sources of airborne particulate matter (PM) using a newly developed approach, Factor Analysis and Poisson Regression (FA/PR). We hypothesized that by adding information on PM chemical speciation and source apportionment to typical PM epidemiological analysis, we could identify PM sources that cause adverse health effects. The FA/PR method was applied to a merged data set of mortality and extensive PM chemical speciation (including trace metals, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 9 publications
1
32
0
6
Order By: Relevance
“…Numerous epidemiological studies have shown that there is an association between PM concentration and various adverse health outcomes (Li, Shao, & Yang, 2006;Tsai, Apte, & Daisey, 2000;Wan Mahiyuddin et al, 2013). Consequently, the assessment of air quality, particularly in terms of PM10 and PM2.5 (PMs with aerodynamic diameters less than 10 and 2.5 μm, respectively) and their compositions, is a pressing issue of the moment.…”
Section: Introductionmentioning
confidence: 98%
“…Numerous epidemiological studies have shown that there is an association between PM concentration and various adverse health outcomes (Li, Shao, & Yang, 2006;Tsai, Apte, & Daisey, 2000;Wan Mahiyuddin et al, 2013). Consequently, the assessment of air quality, particularly in terms of PM10 and PM2.5 (PMs with aerodynamic diameters less than 10 and 2.5 μm, respectively) and their compositions, is a pressing issue of the moment.…”
Section: Introductionmentioning
confidence: 98%
“…One natural progression of the PM health effects research is therefore to conduct a source apportionment of PM using chemical speciation data, and to examine the associations between source-apportioned PM and health outcomes, rather than with PM mass overall. There have been only a few studies that conducted such analyses (Ö zkaynak and Thurston, 1987;Ö zkaynak et al, 1996;Laden et al, 2000;Tsai et al, 2000;(reanalyzed by Schwartz, 2003); Mar et al, 2000(reanalyzed by Mar et al, 2003). These studies have provided some suggestive evidence that PM from certain combustion sources (i.e., secondary aerosols and traffic), but not other sources (e.g., soil), were associated with daily mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Only recently have researchers possessed the tools and technologies to be able to examine the health effects of individual PM components [2][3][4][5][6][7][8][9][10][11] and source types. [12][13][14][15][16][17] These efforts have been based on either traditional factor analysis or a priori source profiles.…”
Section: Introductionmentioning
confidence: 99%